Analisis Pengaruh Variasi Kecepatan dan Karakteristik Roda Penggiling Terhadap Kapasitas Hasil Penggilingan - Dimas Aryaputra; Arya Mahendra Sakti; Dyah Riandadari; Nurul Ainu Sofi (Jurnal Rekayasa Mesin, 2026)
Optimizing the processing of agricultural waste, especially peanut hulls, is a significant challenge in increasing the economic value of food byproducts. This study aims to analyze the performance of a disc mill through experiments exploring two key mechanical parameters: variations in shaft rotational speed and the geometric characteristics of the grinding wheel (number of blades). Experiments were conducted using an FFC-15 machine, where the grinding wheel was varied to 2, 3, and 4 blades, combined with variations in shaft rotational speed of 2400, 2600, and 2800 rpm. The results showed a nonlinear phenomenon, namely that increasing the number of blades did not always increase efficiency. The 4-blade configuration actually caused air turbulence and flow resistance, thus reducing production capacity, while the 2-blade configuration triggered the release of many fine particles. The best performance was achieved with a 3-blade configuration at 2800 rpm, which produced the highest grinding capacity of 0.095 kg per minute. This configuration offers the best balance between impact frequency and material circulation space, thus becoming a technical recommendation for improving the efficiency of the husk waste processing machine.